Implementation of Indonesian Financial Accounting Standards for Private Entities (SAK EP) on XYZ Foundation - Nikomaru, Fauzano; Fatima, Eliza (E-Jurnal Akuntansi, 2025)
This study aims to analyse the impact of implementing SAK EP on the financial statements of Foundation XYZ and identify challenges during the process. Data were collected through documentation and semi-structured interviews with the foundation's financial staff. With qualitative method and case study approach, the findings reveal significant changes in financial reporting, including changes on naming for financial statement, classification of accounts, use of one comprehensive income statement approach, and make Notes to the Financial Statement according to SAK EP. Key challenges include limited understanding of SAK EP and the inadequacy of the accounting system used. This research can be a learning material to make it easier for other foundations to understand the practical application of SAK EP in foundations.  Keywords: Challenges; Financial Statement; Foundation; SAK EP; Impact